Mental Health Services, Free Appropriate Public Education, and Students With Disabilities: Legal Considerations in Identifying, Evaluating, and Providing Services. (April 2018) - Yell, Mitchell; Smith, Carl; Katsiyannis, Antonis; Losinski, Mickey
In the past few years, the provision of mental health services in public schools has received considerable attention. When students with disabilities are eligible for special education and related services under the Individuals With Disabilities Education Act (IDEA), mental health services are required if such services are needed to provide students with a free appropriate public education (FAPE). That is, when a student's individualized education program (IEP) team determines that he or she needs mental health services to receive a FAPE, a school district is required to provide these services. Our purpose is to discuss when school district personnel should identify, evaluate, and serve students with disabilities who may have mental health needs.